2015
DOI: 10.1016/j.nbd.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

SOX11 identified by target gene evaluation of miRNAs differentially expressed in focal and non-focal brain tissue of therapy-resistant epilepsy patients

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally control the expression of their target genes via RNA interference. There is increasing evidence that expression of miRNAs is dysregulated in neuronal disorders, including epilepsy, a chronic neurological disorder characterized by spontaneous recurrent seizures. Mesial temporal lobe epilepsy (MTLE) is a common type of focal epilepsy in which disease-induced abnormalities of hippocampal neurogenesis in the subgranular zone as well as gliosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 71 publications
2
34
0
1
Order By: Relevance
“…mGlu 7 is thought to be a therapeutic target for various CNS disorders; polymorphisms in the GRM7 gene have been linked to autism, depression, bipolar disorder, attention deficit hyperactivity disorder (ADHD), and schizophrenia. 315329 The first reported allosteric agonist of mGlu 7 , AMN082 ( 87 ), demonstrates agonist activity in vitro and was reported to be active in models of stress-related CNS disorders (Figure 25). 330 However, more recent reports suggest that the in vivo activity might involve mechanisms in addition to mGlu 7 .…”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…mGlu 7 is thought to be a therapeutic target for various CNS disorders; polymorphisms in the GRM7 gene have been linked to autism, depression, bipolar disorder, attention deficit hyperactivity disorder (ADHD), and schizophrenia. 315329 The first reported allosteric agonist of mGlu 7 , AMN082 ( 87 ), demonstrates agonist activity in vitro and was reported to be active in models of stress-related CNS disorders (Figure 25). 330 However, more recent reports suggest that the in vivo activity might involve mechanisms in addition to mGlu 7 .…”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…The first genome‐wide profiling study of miRNA expression in human TLE patients compared several epilepsy‐associated cellular processes and found that the immune response was predicted to be the most prominently targeted process by deregulated miRNAs . In particular, miR‐221 and miR‐222 were shown in several reports to be down‐regulated and seem to correlate with endogenous intercellular adhesion molecule 1 (ICAM1) expression in astrocytes from TLE patients . Because ICAM1 is a protein that favors immune and inflammatory responses, these miRNAs might be proinflammatory during epileptogenesis.…”
Section: Mirna Involvement In Neuroinflammation During Epileptogenic mentioning
confidence: 99%
“…Because it has also been reported to be a tumor suppressor when down‐regulated in various types of cancer, loss of miR‐137 might also have effects on cell death during epileptogenesis. Similarly, let‐7 is an miRNA family thought to be involved in cell cycle regulation by promoting differentiation, and multiple let‐7 members have been found deregulated during epileptogenesis by different groups . However, the direction of deregulation is highly variable, depending on the let‐7 isoform considered.…”
Section: Mirna Involvement In Epilepsy‐associated Cell Proliferation mentioning
confidence: 99%
“…[7] There is increasing evidence to support that miRNA changes are involved in the pathophysiology of epilepsy. [8] Using either rodent epilepsy models or human tissue from patients with epilepsy, a number of previous studies have demonstrated that miRNA expression is altered in epilepsy.…”
Section: Introductionmentioning
confidence: 99%